Relationship Between the Frequency of Eating Snack Food and Incidence of Stunting - Rahmaningrum, Frida Indah; Wijayanti, Lumastari Ajeng; Cahyani, Desy Dwi; Sendra, Eny (Journal of Ners and Midwifery, 2025)
Failure to thrive among toddlers results in stunting. One of the contributing factors is not fulfilling nutritional needs. Toddlers prefer to eat snack food with low nutritional content and the sugar content makes children feel full, reducing the portion of food in the main meal schedule that contains balanced nutritional value. The purpose of this study was to determine the relationship between the frequency of consuming snack food and the incidence of stunting. The method in this study used observations with a cross-sectional design. The Population was 232 people, with a sample of 70 mothers of stunted toddlers selected through the Simple Random Sampling technique. The instrument in this study used a questionnaire and was analyzed with the Spearman Rank test with the results (ρ = 0,000 < 0.05) between the frequency of consuming snack food and the incidence of stunting. This study showed a relationship between the frequency of consuming snack food and the incidence of stunting toddlers who consume snack food too often will cause stunting in toddlers. Based on the results, it is recommended that snack foods be given two hours before main meals to help address this issue.